Impact of thyroid autoimmunity and vitamin D on in vitro fertilization/intracytoplasmic sperm injection outcomes among women with normal thyroid function - Liu, Yalong; He, Zining; Huang, Ning; Zeng, Lin; Wang, Yang; Li, Rong; Chi, Hongbin (Frontiers in Endocrinology, 2023)
This prospective cohort study aimed to determine the impact of thyroid autoimmunity and total 25-hydroxyvitamin D concentration on early pregnancy outcomes in women undergoing in vitro fertilization/intracytoplasmic sperm injection who had intact thyroid function. The study included 1,297 women who underwent in vitro fertilization/intracytoplasmic sperm injection cycles, although only 588 patients received fresh embryo transfer. The study endpoints were clinical pregnancy, ongoing pregnancy, ectopic pregnancy, and early miscarriage rates. Our study found that the total 25-hydroxyvitamin D serum concentrations (P<0.001) and anti-Mullerian hormone levels (P=0.019) were lower among patients in the TAI group (n=518) than among those in the non-TAI group (n=779). Additionally, the study population in each group was divided into three subgroups according to the total vitamin D status based on clinical practice guidelines (deficient, <20 ng/mL; insufficient, 21–29 ng/mL; and sufficient, ≥30 ng/mL), TAI group: sufficient, n=144; insufficient, n=187; and deficient, n=187; non-TAI group: sufficient, n=329; insufficient, n=318, and deficient, n=133. In the TAI group, the number of good-quality embryos decreased in patients with vitamin D deficiency (P=0.007). Logistic regression analysis indicated that aging prevented women from achieving clinical (P=0.024) and ongoing pregnancy (P=0.026). The current findings suggest that patients with TAI had reduced serum vitamin D concentration. Furthermore, in the TAI group, the number of good-quality embryos decreased in patients with vitamin D deficiency. Finally, aging adversely impacted achieving clinical and ongoing pregnancy.